Coping mechanisms utilized by children suffering from asthma at Phalombe health centre. - Wataya, Stella Maluwa (Kamuzu University of Health Sciences, 2022)
The study is on coping mechanisms utilized by children suffering from asthma. The purpose of the current study is to explore coping mechanisms utilized by patients suffering from asthma that can play a role in how the patients adapt to the disease. The study will be conducted at Phalombe health centre in Phalombe district. The study will use qualitative method. Roy's Adaptation model will be used in the study: A convenient sample of 10 patients at the out-patient department will be recruited for the study. The participants will be interviewed using an interview guide. Data collected will be analysed using content analysis.